Lost and found: recovery of the holotype of the ocellated angelshark, Squatina tergocellatoides Chen, 1963 (Squatinidae), with comments on western Pacific squatinids - Theiss, Susan M.; Ebert, David A. (Zootaxa, 2013)
The ocellated angelshark, Squatina tergocellatoides, Chen, 1963 is redescribed from the holotype, which was thought to be lost. Its recent recovery has allowed for a revised description, including new data, and comparison to other Western Pacific squatinids. Squatina tergocellatoides can be distinguished from its congeners by three pairs of prominent large black spots, each with a diameter greater than eye length; two on each pectoral fin at anterior and posterior angles and one on each side near the tail base; another three pairs of lesser defined spots, one large spot on base of each dorsal fin and one located laterally on each side of tail located below first dorsal fin. Ventral surface is uniformly white to cream coloured, and margins of pectoral fins and tail similar in colour to dorsal side. Pectoral fins with angular lateral apices and rounded posterior lobe, pelvic fin tips not reaching origin of first dorsal fin, strongly fringed nasal barbels, small inter-orbital space, head and mouth lengths, broad internarial width and pelvic fin base, a very small pelvic girdle width, and a caudal fin with triangular ventral lobe greater in length than dorsal lobe. Comments on additional specimens are provided, as well as observations on biogeography. A review of western Pacific squatinids is also provided.